Axillary reverse mapping in breast cancer surgery - functional study - Pavlista, David; Dostalek, Lukas; Velenska, Zuzana (Neoplasma, 2022)
The aim of the study was to map the lymphatic drainage of the upper extremity that traverses the axilla and elucidate its relationship with the lymphatic drainage of the breast. In 79 breast cancer patients indicated to the axillary lymph node dissection for category cN1, cN2, Technetium-99m (particle size <80 nm) was applied prior to surgery at two injection sites between the second and third metacarpophalangeal joints to visualize upper extremity lymphatics. During the surgery, the axilla was anatomically divided into 6 quadrants. A C-Trak® device was used for the intraoperative detection of radioactivity. After verifying activity, the nodes were resected and their position was recorded. Active nodes were sent separately according to topographic localizations for microscopic examination. All affected nodes (both macro- and micrometastases) were recorded as positive. The location, involvement and radioactivity, and the number of lymph nodes obtained were analyzed. In total, 1,109 lymph nodes were removed and examined. Radioactive nodes were found in all 79 patients. A total of 230 radioactive nodes were found. 21 nodes were both radioactive and metastatically affected. Results show that part of the lymph from the upper extremity flows through the nodes in the central part of the axilla and mixes with the lymph from the breast. This suggests that lymphatic drainage of the upper limb cannot be functionally separated from lymphatic drainage of the breast. The results also explain the possible mechanical cause of arm lymphedema after sentinel lymph node biopsy.
Keywords: Lymphedema; nádory prsu; biopsie sentinelové lymfatické uzliny; lymfadenektomie; Female; Axilla; axila; Breast Neoplasms; Lymph Nodes; mastektomie; lymfatické uzliny; ženské pohlaví; Humans; lidé; Sentinel Lymph Node Biopsy; Mastectomy; Lymph Node Excision; lymfedém